Komodifikasi Pendidikan dalam Masyarakat Kapitalis: Kajian Literatur Kritis - Adiyasa, Arya; Irfani Lindawati, Yustika (CV. PUSDIKRA MITRA JAYA, 2025)
Education is meant to be a space of emancipation, a place where individuals can grow and develop free from economic or social barriers. Yet in the reality of capitalist societies, education has gradually shifted into a commodity something to be bought, sold, and evaluated through the lens of profit and loss. This article explores that transformation through a critical literature review, drawing on the works of thinkers such as Apple, Bourdieu, Becker, and Giroux. Using a qualitative approach within the framework of sociology of education, this study finds that the commodification of education not only creates inequality in access and quality but also erodes the humanistic values of the learning process. Education becomes an arena of economic selection, rather than a right inherent to all. Even so, spaces of resistance persistin the form of social movements, critical pedagogy, and community-based educational models rooted in justice. This article underscores the urgency of reclaiming education as a means of liberation, not merely as a tool for producing labor.